The Impact of the Interaction between Madden-Julian Oscillation and Cold Surge, on Rainfall over Western Indonesia - Agita Vivi Wijayanti; Rahmat Hidayat; Akhmad Faqih; Furqon Alfahmi (Indonesian Journal of Geography, 2021)
The Madden-Julian Oscillation and Cold Surge phenomena have been known to cause increased rainfall, with the capacity to trigger hydrometeorological disasters, in western Indonesia. However, further investigations are required regarding the interaction between these phenomena on rainfall pattern. Therefore, this study aims to analyze the interaction between MJO and CS over western Indonesia, particularly by using land-based rainfall observation data from multiple stations, as previous studies were dominated by the use of gridded data from remote observations. This study utilized in-situ observation data obtained from 4329 weather observations and rain stations between 1989 and 2018.  Subsequently, quality control performed based on data availability exceeding 70% over a 30-year period resulted in 303 selected stations to be used for further analysis. Meanwhile, the RMM index, as well as reanalysis data of mean sea level pressure and 925 hPa meridional wind, were also applied for MJO and CS identification. According to the composite analysis, the effect of CS on MJO phases tends to increase precipitation by about 50%, over western Indonesia, with maximum increase ranging from 200 to 400% over the northeastern coast of Sumatra, around Karimata Strait (Riau Islands and West Kalimantan), as well as the northern coast of Java. These areas are exposed to the sea and have direct access to the wind-terrain interaction. In addition, the highest rainfall anomaly due to the MJO-CS interaction occurs around Karimata Strait, followed by northern Sumatra and Java, with spatially averaged rainfall anomaly reaching 5 mm/day over the area.